Postponing And Aborting Pregnancy In Light Of Corona Virus Outbreak And Its Epidemic Strains From The Perspective Of Sharia Rules And Purposes - Muneer Ali Abdul Rab; Baidar Mohammed Mohammed Hasan; Mahmoud Mohamed Ali Mahmoud Edris; Lutfi Muhammad Zain; Mesbahul Hoque (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite